Analisis Kinerja Guru Pendidikan Jasmani Olahraga dan Kesehatan terhadap Motor Ability dan Hasil Belajar pada Siswa SD Negeri di Kabupaten Pinrang - Sahabuddin, Sahabuddin; Hakim, Hikmad; Binsar, Ahmad Rum (Journal Coaching Education Sports, 2020)
Abstract This study aims to determine the results of the performance contribution of physical and health physical education teachers to motor ablity and learning outcomes in state elementary school students in Pinrang Regency. This research is a type of correlational research. The population is male elementary school students in Pinrang Regency with a sample of 100 students with cluster random sampling techniques. The data analysis technique used is multiple correlation. Based on these results it can be concluded that (1) There is a contribution of the performance of physical and health physical education teachers to motor abilities in state elementary school students in Pinrang Regency by 57.1%, this result shows that the performance of physical and physical education teachers has a contribution to the motor ability of state elementary school students in Pinrang Regency, and (2) There is a contribution of the performance of physical and health physical education teachers to the learning outcomes of elementary school students in Pinrang Regency by 71,5%. These results indicate the analysis that the performance of physical and health physical education teachers has a contribution to the learning outcomes of elementary school students in Pinrang Regency. Keywords: Performance, Teacher, Motor Ability, Learning Outcomes Abstrak Penelitian ini bertujuan untuk mengetahui hasil kontribusi kinerja guru pendidikan jasmani olahraga dan kesehatan terhadap motor ablity dan hasil belajar pada murid SD Negeri di Kabupaten Pinrang. Penelitian ini adalah jenis penelitian korelasional. Populasinya adalah siswa putra SD Negeri di Kabupaten Pinrang dengan sampel berjumlah 100 orang siswa dengan teknik cluster random sampling. Teknik analisis data yang digunakan adalah korelasi ganda. Berdasarkan hasil tersebut dapat disimpulkan bahwa (1) Ada kontribusi kinerja guru pendidikan jasmani olahraga dan kesehatan terhadap motor ability pada murid SD Negeri di Kabupaten Pinrang sebesar 57,1%, Hasil ini menunjukkan bahwa kinerja guru pendidikan jasmani olahraga dan kesehatan memiliki kontribusi terhadap motor ability murid SD Negeri di Kabupaten Pinrang, dan (2) Ada kontribusi kinerja guru pendidikan jasmani olahraga dan kesehatan terhadap hasil belajar pada murid SD Negeri di Kabupaten Pinrang sebesar 71,5%. Hasil ini menunjukkan analisa bahwa kinerja guru pendidikan jasmani olahraga dan kesehatan memiliki kontribusi terhadap hasil belajar murid SD Negeri di Kabupaten Pinrang. Kata kunci: Kinerja, Guru, Motor Ability, Hasil Belajar